2017
DOI: 10.1590/s0102-865020170100000009
|View full text |Cite
|
Sign up to set email alerts
|

Study of the protective effect of dexamethasone on cisplatin-induced ototoxicity in rats

Abstract: Study of the protective effect of dexamethasone on cisplatininduced ototoxicity in rats 1 9-Experimental SurgeryActa Cir Bras. 2017;32(10):873-880 AbstractPurpose: To evaluate the ability of dexamethasone to protect against cisplatin (CDDP)-induced ototoxicity. Methods: Male Wistar rats were divided into the following three groups: 1) Control (C): 6 animals received intraperitoneal (IP) saline solution, 8 ml/kg/day for four days; 2) C + CDDP: 11 animals received 8 ml/kg/day of IP saline and, 90 min after salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous studies had reported a protective effect of DEX against cisplatin-induced cytotoxicity, while such an effect was not observed in a clinical trial by transtympanic injection.This discrepancy noted between in vitro and clinical studies may be due to the lack of sufficient DEX concentration in the inner ear 2628. In the present study, we utilized a drug-loaded silk hydrogel as a drug storage system in order to improve the drug concentration in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported a protective effect of DEX against cisplatin-induced cytotoxicity, while such an effect was not observed in a clinical trial by transtympanic injection.This discrepancy noted between in vitro and clinical studies may be due to the lack of sufficient DEX concentration in the inner ear 2628. In the present study, we utilized a drug-loaded silk hydrogel as a drug storage system in order to improve the drug concentration in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…The limiting side effects of its use include nephrotoxicity, neurotoxicity, and ototoxicity (Daldal et al 2007; Rybak et al 2009). Although nephrotoxicity can be controlled and reduced by hydration therapy, no preventive treatments for ototoxicity are currently known (Capelo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tested model of acute kidney injury by HS was established according to (Chen et al, 2015b). Doses of Dexa and EGCG were selected as sub-toxic doses, referring to (Capelo et al, 2017) and (Kumaran et al, 2009), respectively.…”
Section: Heat Stress Protocolmentioning
confidence: 99%